Development and Validation of Rabies Health Education Module (RaHEM) for Dog Owners in Kelantan, Malaysia: An ADDIE Model - Mohammad Fazrul Mohammad Basir; Suhaily Mohd Hairon; Mohd Ismail Ibrahim; Wan Mohd Zahiruddin Wan Mohamad; Nik Mohd Hafiz Mohd Fuzi; Ainin Syakirah Rosli; Mohammad Sabri Abdul Rahman; Anas Rosedi (Journal of Epidemiology and Global Health)
Abstract Background Rabies is a preventable yet deadly public health threat. Despite the availability of effective vaccines for both humans and animals, the persistence of rabies-related fatalities underscores the need for enhanced public education strategies. This study aimed to develop and validate a Rabies Health Education Module delivered via a Massive Open Online Course, targeting adult dog owners in Kelantan, Malaysia. Methods The development of RaHEM followed the ADDIE framework. A comprehensive analysis was conducted through literature reviews, cross-sectional surveys, and stakeholder interviews. The module’s content was designed and developed based on the Modified Health Belief Model and Mayer’s Cognitive Theory of Multimedia Learning. Validation was performed by a panel of six experts and ten dog owners through content and face validity indices, respectively. Results The module was organized into five core topics, each addressing specific aspects of rabies prevention. Content validity indices for all topics exceeded the acceptable threshold of 0.83, with an overall module CVI of 0.91 for relevance and 0.88 for clarity. Face validity indices also surpassed the 0.83 threshold, with overall module FVI scores of 1.00 for understandability and 0.99 for clarity. Conclusion The RaHEM MOOC was successfully developed and thoroughly validated, ensuring it met its intended objectives and was suitable for the target audience. This educational module offers a promising approach to enhancing rabies prevention through accessible and engaging online education, potentially contributing to reduced rabies transmission and fatalities. Further studies are recommended to evaluate the module’s effectiveness in improving rabies knowledge and attitudes.